Diabetes-Resistant NOR Mice Are More Severely Affected by Streptozotocin Compared to the Diabetes-Prone NOD Mice: Correlations with Liver and Kidney GLUT2 Expressions - S. Kahraman; C. Aydin; G. O. Elpek; E. Dirice; A. D. Sanlioglu (Journal of Diabetes Research)
Nonobese Diabetic (NOD) mice are susceptible strains for Type 1 diabetes development, and Nonobese Diabetes-Resistant (NOR) mice are defined as suitable controls for NOD mice in non-MHC-related research. Diabetes is often accelerated in NOD mice via Streptozotocin (STZ). STZ is taken inside cells via GLUT2 transmembrane carrier proteins, the major glucose transporter isoforms in pancreatic beta cells, liver, kidneys, and the small intestine. We observed severe adverse effects in NOR mice treated with STZ compared to NOD mice that were made diabetic with a similar dose. We suggested that the underlying mechanism could be differential GLUT2 expressions in pancreatic beta cells, yet immunofluorescent and immunohistochemical studies revealed similar GLUT2 expression levels. We also detected GLUT2 expression profiles in NOD and NOR hepatic and renal tissues by western blot analysis and observed considerably higher GLUT2 expression levels in liver and kidney tissues of NOR mice. Although beta cell GLUT2 expression levels are frequently evaluated as a marker predicting STZ sensitivity in animal models, we report here very different diabetic responses to STZ in two different animal strains, in spite of similar initial GLUT2 expressions in beta cells. Furthermore, use of NOR mice in STZ-mediated experimental diabetes settings should be considered accordingly.